Sympathetic feedback cooling in the optomechanical system consisting of two coupled cantilevers - Gong, Zhi-Cheng; Shen, Cheng-Yu; Yuan, Quan; Sun, Chang-Pu; Li, Yong; Fu, Hao (Frontiers in Physics, 2023)
We present sympathetic cooling in an optomechanical system consisting of two coupled cantilevers. The hybridization of the cantilevers creates a symmetric mode, which is feedback cooled, and an anti-symmetric mode beyond directly controllable by the feedback. The scheme of sympathetic cooling is adopted to cool the anti-symmetric mode indirectly by parametrically coupling to the feedback-cooled symmetric mode, from which the cooling power can be transferred. Experiment shows that the realization of coherent dynamics plays an essential role in sympathetic cooling, in which optimal cooling is achieved when the mechanical dissipation rate and the strength of coupling become comparable. The sympathetic cooling is improved by increasing the strength of mode coupling to enhance the transfer of cooling power. And the limit of sympathetic cooling imposed by the capacity of feedback cooling is reached as the effective temperatures of the two modes approaching at the strong coherent coupling condition. Our research provides the prospect of extending the cooling techniques to coupled mechanical resonators for a broad application in sensing and information processing.